2012
DOI: 10.1080/07315724.2012.10720443
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acids Improve Glucose Metabolism without Effects on Obesity Values and Serum Visfatin Levels in Women with Polycystic Ovary Syndrome

Abstract: Omega-3 fatty acids improved insulin sensitivity in PCOS patients. This beneficial effect was not associated with alteration in anthropometric measurements and serum visfatin levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 52 publications
(91 reference statements)
1
45
0
5
Order By: Relevance
“…Dietary factors, including anti-inflammatory foods may have a key role in improving metabolic disorders of PCOS [7]. The beneficial effects of omega-3 fatty acids from flaxseed oil on insulin resistance, inflammation and oxidative stress have previously reported in few studies.…”
Section: The Effects Of Flaxseed Oil Omega-3 Fatty Acids Supplementatmentioning
confidence: 99%
“…Dietary factors, including anti-inflammatory foods may have a key role in improving metabolic disorders of PCOS [7]. The beneficial effects of omega-3 fatty acids from flaxseed oil on insulin resistance, inflammation and oxidative stress have previously reported in few studies.…”
Section: The Effects Of Flaxseed Oil Omega-3 Fatty Acids Supplementatmentioning
confidence: 99%
“…Women with polycystic ovarian syndrome and BMI between 25 and 40 kg/m 2 , however, exhibited no significant changes in BMI after supplementation for 8 weeks [60]. The period of treatment in this study may not be long enough to observe significant anthropometric changes after omega-3 administration with no other associated instruction or intervention.…”
Section: Discussionmentioning
confidence: 91%
“…which pointed out toward insignificant effects of omega-3 fatty acid therapy on anthropometrics profile. [38] Therapy with omega-3 fatty acid in patients with CAD led to significant increases in adiponectin serum levels compared to control with significant improvement in HOMA-IR, HOMA-β, insulin levels, and fasting blood glucose, these findings were inconsistent with Yamamoto et al . results which revealed that administration of omega-3 fatty acid produced significant anti-inflammatory effects in patients with CAD associated with hyperlipidemia through an increase in adiponectin serum levels.…”
Section: Discussionmentioning
confidence: 99%